1989
DOI: 10.1002/1097-0142(19890301)63:5<935::aid-cncr2820630525>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of metastasis in uterine sarcoma. An autopsy study

Abstract: The autopsy findings of 73 patients with uterine sarcoma were studied to determine the sites and possible modes of metastasis. Homologous mixed mesodermal tumors were the most frequent (41%) followed by leiomyosarcoma (26%), heterologous mixed mesodermal tumor (18.3%), stromal sarcoma (12%), and endolymphatic stromal myosis (3%). The peritoneal cavity and omentum were the most frequently involved sites (59%), followed by the lung (52%), pelvic lymph nodes (41%), paraaortic lymph nodes (38%), and liver parenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
1
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(55 citation statements)
references
References 12 publications
2
51
1
1
Order By: Relevance
“…The risk of recurrence after complete resection of uterus-limited LMS, which was estimated to be 70% after 2 years in a retrospective study, is high (Major et al, 1993 Feb 15). The most common sites of uterine LMS metastasis are the lung, pelvis, and vagina (Rose et al, 1989 Mar 1, Mayerhofer et al, 1999 Aug), but brain metastasis is rare. To the best of our knowledge, only case reports of uterine LMS metastasis to the brain are available (Wroński et al, 1994 Aug, Honeybul and Ha, 2009 Mar, Yamada et al, 2011 Dec).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of recurrence after complete resection of uterus-limited LMS, which was estimated to be 70% after 2 years in a retrospective study, is high (Major et al, 1993 Feb 15). The most common sites of uterine LMS metastasis are the lung, pelvis, and vagina (Rose et al, 1989 Mar 1, Mayerhofer et al, 1999 Aug), but brain metastasis is rare. To the best of our knowledge, only case reports of uterine LMS metastasis to the brain are available (Wroński et al, 1994 Aug, Honeybul and Ha, 2009 Mar, Yamada et al, 2011 Dec).…”
Section: Discussionmentioning
confidence: 99%
“…Yamada et al reviewed in their case report that there had been 21 such cases (Yamada et al, 2011 Dec). Brain metastasis incidence has been reported to be 1 in 19 (Rose et al, 1989 Mar 1) and 1 in 4 from autopsies of patients with uterine LMS (Fleming et al, 1984 Oct). In a retrospective study of brain metastases from gynecologic malignancies, 4 cases out of 139 cases of gynecologic malignancies were uterine LMS (Nasu et al, 2013 Feb).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distant metastases arrive late in the disease and the predilection sites are lungs, liver, kidneys and skin through hematogenous dissemination. Although rare, cases of uterine leiomyosarcoma with skeletal metastasis have been reported in the literature (Rose et al, 1989, Ziewacz et al, 2012). Lipoleiomyosarcoma is a rare subtype containing both leiomyosarcomatous and lipomatous components.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in surgery, radiation and the development of novel chemotherapeutic agents have led to prolonged survival and an increase in the prevalence of bone metastasis [2]. The incidence of bone metastasis secondary to endometrial cancer is reported to be 6 to 15% [3,4]. Bone metastases occur in approximately 1.2% of patients with ovarian cancer [5] and represent the third most common site of metastasis in cervical cancer, occurring in 1.1% of patients [6,7].…”
Section: Introductionmentioning
confidence: 99%